Pengaruh Konten Marketing Terhadap Minat Beli Pengguna Tik Tok Shop - Alfi Antika; Lu' Lu Ul Maknunah (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
In marketing communications there is a marketing mix, one of which is promotion. Content marketing is said to be a marketing strategy by creating or creating content that is solicitation with the aim of providing information to potential customers. With a good and appropriate content marketing strategy then create a positive and good image for a product or service brand in order to attract buying interest from target consumers. This study used the Disproportionate Stratified Random Sampling technique (stratified random disproportionate sampling), with the target of students of the Social and Political Faculty of Balitar Blitar Islamic University, a total population of 140 students and a sample of 136 students. Data collection techniques were field observations, literature studies and questionnaires. The results of the research from various tests that have been carried out on 140 respondents to answer the statements that have been submitted, in this study there is a conclusion that the relationship between Marketing Content (X) and Purchase Intention (Y) has a positive or significant effect.